A confirmatory factor analysis of the information technology governance effectiveness: evidence from Malaysia - Jasber, Kaur; Mohamed, Norshidah; Ahlan, Abdul Rahman (2011)
This research seeks to tests the reliability and construct validity of the information technology governance effectiveness. The population comprises the highest ranking IT personnel in Malaysian private organizations. Results from confirmatory factor analysis which utilizes structural equation modeling techniques, confirm a model for IT governance that comprises structure, process and relational mechanisms.